An Approximation to Elections in Mexico during the XIX c. (2017)
This article reflects on the meaning and importance of nineteenth century electoral practices in Mexico. We offer a general idea of the constitution of the electoral institution during this period, configuring a political culture based on suffrage. As a mechanism linked to the sovereignty of the people and to political representation, the election process constituted the source of legitimacy of every Republican regime, as well as a space of fundamental political negotiation for the construction of political powers and the governability of the new nation. In these pages we present some of theprincipal normative frameworks that legislated national electoral processes throughout the XIX c. in Mexico, allowing a close examination of certain suffrage practices as a wayto understand the values and meanings that the population conferred to the elections.